Hubungan Antara Frekuensi "Ngemil", Durasi Menonton TV dan Durasi Bermain Games Dengan Kejadian Overweight Pada Remaja di SMP Negeri 5 Karanganyar. - Wicaksono, Edo Yulianto, Fitriana Mustikaningrum, S.Gz, M.Sc, Pramudya Kurnia, STP, M.Agr (2015)
Introduction: The number of overweight has been increasing throughout the world, so that it become a health problem. Overweight can be caused by several factors including the frequency of "snacking", the duration of watching TV and the duration of playing games.Objective: The aims of study to investigate the relationship between the frequency of "snacking", duration of watching TV and duration of playing games with the incidence of overweight in adolescents in SMP Negeri 5 Karanganyar junior high school.Research methods: this type of research was observational crosssectional method. Sampling techniques used as proportional stratified random sampling methods. The respondents in this study are 38 overweight students and 38 normal students. The frequency of "snacking" obtained using questionnaire FFQ. The statistic data was analysed by Chi-Square test.Results : The data presents the proportion of frequency of "snacking" was 51.3% as often category. The proportion of duration of watching TV was 59.5% as rarely category. The proportion of duration of playing games was 50.5% as rarely category. Bivariate analysis with Chi-Square that the p-value for frequency of "snacking" was 0.818, while p-value of duration of watching TV was 0.108 and p-value of duration of play games was 0.783.Conclusion : There was no relationship between the frequency of "snacking", duration of watching TV and duration of playing games with overweight incidents in SMP 5 Karanganyar Junior High School.